2011
DOI: 10.2355/isijinternational.51.889
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Dissolution in the TiO2–SiO2–FeO and TiO2–SiO2–MnO Based Welding-Type Fluxes

Abstract: The hydrogen solubility of TiO2-SiO2-FeO and the TiO2-SiO2-MnO welding-type flux systems have been studied to identify and compare the hydrogen dissolution behavior in molten welding fluxes at high temperatures of 1 823 K in a wide range of compositions. The dependence of the water vapor pressure and the hydrogen solubility showed a slope of 1/2 suggesting thermodynamic equilibrium was obtained. For an acidic slag composition, the hydrogen was found to be incorporated within the silicate network structure and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Verification and reproducibility of the hydrogen analysis has been provided in a previously published paper. 20) …”
Section: Methodsmentioning
confidence: 99%
“…Verification and reproducibility of the hydrogen analysis has been provided in a previously published paper. 20) …”
Section: Methodsmentioning
confidence: 99%
“…(2) The Effect of the FeO t Content on the Slag Structure at Fixed CaO/SiO 2 Ratios Using FTIR Our previous work 55,56 showed that the dissolution of hydrogen in slag is affected by the degree of slag polymerization and the number of available reaction sites. This polymerization and slag networking effect was ascertained by FTIR and Raman spectroscopy, similarly to Mysen et al [47][48][49] and McMillan.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the slag can pick up hydrogen and water vapor, then transfer it to the liquid metal. Many studies [47][48][49][50] have been done to investigate the solubility of hydrogen in slags. Walsh et al [43] studied the solubility of hydrogen in steelmaking slags.…”
Section: Solubility Of Hydrogenmentioning
confidence: 99%